Manx Latin: A Further Distinctive of the Island? - Harvey, Anthony (Studia Celtica Posnaniensia, 2025)
Over the past two generations, scholars of Manx have worked patiently to rehabilitate scholarly appreciation of traditional Manx as a fully valid Gaelic language; it was not merely an aberrant version of the tongues known from Ireland and Scotland, nor had it lost its integrity through anglicization. The question is now whether the Island’s extant latinity deserves an analogous reappraisal. Since the Dictionary of Medieval Latin from Celtic Sources (DMLCS) programme adopted into its corpus the Manx synodal statutes of the 13th/14th centuries, the choice of wording found therein has repeatedly turned out to be different from that selected for parallel ecclesiastical legislation elsewhere, even when the intended meaning was similar. This shows up in the semantics of specific items of vocabulary but also, most strikingly, in these texts’ readiness to use rare Latin words, including ones apparently unique to Mann. The paper applies DMLCS methods of systematic word-searching and analysis to Cheney’s definitive 1984 edition in an attempt to determine just what philological position the Statutes occupy within the spectrum of Celtic and wider medieval latinity. A parallel is then drawn with the later establishment of Manx vernacular literacy and its subsequent remarkable tenacity; a contrast is adduced with the very different fate of traditional Cornish, and an underlying reason for the difference is proposed.